Media reports a library disaster: a case study at Colorado State University - Ernest, Douglas, 1947-, author; Lederer, Naomi, 1965-, author (Colorado State University. Libraries, 2000)
The first section of this article surveys the literature regarding the news media's reporting of disasters. The second section describes the media reports of the July 1997 natural disaster's impact upon Morgan Library at Colorado State University. The third section analyzes the reports from Colorado State University's disaster as compared to the research literature, media by media: broadcast, national newspapers and wire services, Colorado (local) newspapers, library press, and specialized publications. The conclusion presents concerns about media reporting and the apparent lack of concern for accuracy; this case study serves as a warning to all librarians and researchers.
Keywords: Colorado State University -- Morgan Library -- Floods; Floods -- Press coverage -- Colorado -- Fort Collins